The burden of nonadherence among adults with asthma: a role for shared decision‐making. Issue 5 (27th January 2017) - Pollard, S.; Bansback, N.; FitzGerld, J. M.; Bryan, S.
Abstract: A shared approach to decision‐making framework has been suggested for chronic disease management especially where multiple treatment options exist. Shared decision‐making (SDM) requires that both physician and patients are actively engaged in the decision‐making process, including information exchange; expressing treatment preferences; as well as agreement over the final treatment decision. Although SDM appears well supported by patients, practitioners and policymakers alike, the current challenge is to determine how best to make SDM a reality in everyday clinical practice. Within the context of asthma, adherence rates are poor and are linked to outcomes such as reduced asthma control, increased symptoms, healthcare expenditures, and lower patient quality of life. It has been suggested that SDM can improve treatment adherence and that ignoring patients' personal goals and preferences may result in reduced rates of adherence. Furthermore, understanding predictors of poor treatment adherence is a necessary step toward developing effective strategies to improve the patient‐reported and clinically important outcomes. Here, we describe why a shared approach to treatment decision‐making for asthma has the potential to be an effective tool for improving adherence, with associated clinical and patient‐related outcomes. In addition, we explore insights into the reasons why SDM has not been implemented into routine clinical practice.